Pelatihan Calon Pengurus, Pengawas, dan Manajer Koperasi Merah Putih Desa Dlanggu, Mojokerto - Muhammad Taufiq Hidayat; Samsi, Nur (Jurnal Pengabdian Masyarakat, 2025)
Cooperatives play a strategic role in strengthening the community economy based on participation and family principles. In Dlanggu Village, Mojokerto Regency, cooperative institutions have not developed optimally due to managerial limitations and understanding of governance. This activity aims to increase the capacity of prospective administrators, supervisors, and managers of the Red and White Cooperative through competency-based training and participatory mentoring. The research used a descriptive qualitative approach with a participatory method, involving 15 participants from the community, MSME actors, and village officials. Data were obtained through observation, interviews, documentation, and questionnaires before and after training, then analyzed using the Miles, Huberman, and Saldaña models through data reduction, presentation, triangulation, and conclusion drawn. The results showed a significant increase in the managerial competence of the participants, especially in the aspects of governance, financial administration, and the application of the principles of Good Cooperative Governance (GCG). Participants understand the importance of transparency, accountability, and independence in cooperative management. In addition to technical improvements, this training strengthens social bonding, collective responsibility, and community social capital. Synergy between members, administrators, and supervisors has been proven to increase the trust and effectiveness of cooperative institutions. This program is a model for strengthening capacity based on community participation that can be replicated in other villages.